Filologia e storia: Come uno storico può aiutare il filologo a interpretare le parole di Gesù - Jossa, Giorgio (Henoch, 2022)
The historian needs the philologist for the correct interpretation of the text, but the philologist must turn to the historian for a more secure and thorough understanding of it. This is all the more true for the text of the synoptic gospels, where the words of Jesus, which were uttered in a specific Jewish context, may have been interpreted by the evangelists, who were by then living in a Greco-Roman context, in a different meaning from the original one. The article discusses four chosen issues of terminology or understanding raised by the canonical gospels to exemplify how, in order to understand these writings, a thorough philological examination is necessary, but must always be complemented by a historical problematisation.